Bricked vaults of the 18th century Valencian hall churches: graphical representation, constructive and pathological analysis - Beatriz Saez Riquelme (Vitruvio: International Journal of Architectural Technology and Sustainability, 2018)
The efficient recovery of historic buildings is only possible through a deep knowledge of traditional construction systems. This article focuses on the study and analysis of the vaults of a group of temples located in the Spanish Levante region, the Valencian hall churches, inspired by the European architectural model known as “Hallenkirche”. Erected during the second half of the 18th century, to the north of the Valencian Community, they make up a constructive group limited in space and time, likely to constitute an ideal entity for investigation. The peculiarity of this type of churches lies in its vaults, which spring from a common height. The main contribution of this research is its graphically schematized constructive classification, as well as the unveiling of their composition and the verification of the use of various counterfort systems. This study concludes with the analysis of the aforementioned vaults pathologies, derived from possible structural movements and expressed in the form of fissures, providing the classification thereof based on their location, and quantifying and assessing them. In order to achieve the stated objectives, it has been necessary to carry out technical inspections of the vaults, both from their intrados and extrados, obtaining data through its direct intake and through deduction methods.